216 Ficus Benjamina Sensitization in Adult Patients with Rhinitis - González-Díaz, Sandra (World Allergy Organization Journal, 2012)
BACKGROUND: In Monterrey there are a considerable number of Ficus benjamina trees, but the awareness-related information to this plant is scarce. The objective of this study is to determine the frequency of sensitization to Ficus benjamina in patients with rhinitis who were attended the Regional Centre of Allergy and Clinical Immunology of Monterrey, Mexico. METHODS: Observational, transversal and descriptive study. We included patients over 18 years old with chronic rhinitis, which completed a questionnaire to assess exposure to Ficus benjamina. Skin prick tests (SPT) to common aeroallergens in our region with extract of Ficus benjamina (Allerstand Company) had done in all subjects. RESULTS: A total of 177 patients were included, mean age was 38 years, 65% (115) were female, 135 (76%) reported contact with a Ficus benjamina tree in their home or neighbor. 12 (17%) patients had a positive skin test to Ficus benjamina, but up to 15% (26) had clinical manifestations when they were close to a tree of Ficus benjamina. Most patients with positive skin test to Ficus benjamina (76.9%, 9) had positive test more than one of the aeroallergen tested. The association between Ficus benjamina and sensitization to other aeroallergens, as well as the symptoms associated to the contact with the tree was not statistically significant. CONCLUSIONS: Sensitization to Ficus benjamina is common and was similar to that reported in European countries. To demonstrate the association between sensitization to Ficus benjamina and symptoms should be made studies with nasal challenge test.